2020
DOI: 10.1007/s42452-020-2702-7
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly synthesis of silver nanoparticles using leaf extract of Flemingia wightiana: spectral characterization, antioxidant and anticancer activity studies

Abstract: In the present investigation, we report simple, robust and eco-friendly synthesis of silver nanoparticles (AgNPs) using leaf extract of Flemingia wightiana. The leaf extract of F. wightiana acts as reducing agent which reduces the silver ions into FW-AgNPs, as well as stabilizing agent by capping around them. Biosynthesized FW-AgNPs were characterized by different spectroscopic techniques. UV-Vis spectrum showed the characteristic SPR peak between 380 and 460 nm. EDX analysis revealed the presence of metallic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 66 publications
(85 reference statements)
3
5
0
Order By: Relevance
“…Ds-AgNPs. Similar results were reported on FTIR analysis by biosynthesized silver nanoparticles by other plant resources 33 36 .
Figure 2 ( a ) FTIR spectrum of the Drosera spatulata plant extract.
…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Ds-AgNPs. Similar results were reported on FTIR analysis by biosynthesized silver nanoparticles by other plant resources 33 36 .
Figure 2 ( a ) FTIR spectrum of the Drosera spatulata plant extract.
…”
Section: Resultssupporting
confidence: 88%
“…The cell lines were maintained at 37 °C in presence of 5% CO 2 atmosphere in an incubator. The cytotoxic assay was carried out by our previous protocol explained in recent research articles 35 , 36 , 40 with different concentration of Ds-AgNPs. Approximately 2 × 10 4 HT-29 colon cancer cells were seeded in each well of 96 well culture plate containing 100 µL of medium.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrophilic functional groups of flavonoids bound to Ag + yield colloid-stable GA-AgNPs in aqueous medium. Crystalline structure of GA-AgNPs was evident in XRD analysis and was similar to the other plant based AgNPs 37 .…”
Section: Discussionsupporting
confidence: 68%
“…The synthesized silver nanoparticles showed that the nanoparticles held about 85% silver and 15% oxygen. Similarly, Netala et al [ 32 ] reported that silver nanoparticles synthesized using Flemingia wightianas extract had a silver content of 41%.
Fig.
…”
Section: Resultsmentioning
confidence: 99%